FORMATION OF STUDENTS' DIDACTIC COMPETENCE IN THE PROCESS OF SELF-DEPENDENT WORK - T. I. Shukshina; Zh. A. Movsesyan (Moscow Polytechnic University, 2017)
The changes in the system of Russian education set new requirements for the graduates of a pedagogical university, focused on the development of student's personality, self-sufficiency in making responsible decisions. The solution of this problem is associated with the formation of didactic competence as an important component of teacher's professional competence. In accordance with these provisions, it becomes necessary to elaborate a model for the effective formation of teacher training students' didactic competence in the process of self-dependent work. The authors describe the components of this model which integrates target, methodological, content, procedural, and diagnostic units.